Monetary Policy Analysis in Serbia - Vesna Martin (Journal of Central Banking Theory and Practice, 2015)
The paper focuses on analysing monetary policy in Serbia. The National Bank of Serbia chose inflation targeting, which sets price stability as the main objective of monetary policy. To achieve this goal, the central bank uses different monetary policy instruments which analysis can provide us with the understanding of the main directions of their actions but also of the limitations of its application. Only through improvement of both instruments and monetary policy the central bank will create a better foundation for achieving monetary stability. In addition, the implementation of exchange rate policy is entrusted to the National Bank of Serbia, as the main regulator of the financial system. A mere use of managed floating exchange rate, as the chosen exchange rate regime, is an appropriate solution in the current economic circumstances and in accordance with the desired objective of monetary policy.
Keywords: 43; 52; 58; 61; 63; 65; 330; monetary policy and its instruments; price stability; dinarisation; foreign exchange market; the exchange rate policy